2005
DOI: 10.1182/blood.v106.11.550.550
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pharmacogenetics and Clinical Factors To Predict the Maintenance Dose of Warfarin.

Abstract: Background Initiation of warfarin therapy using trial-and-error dosing can cause bleeding. Clinical factors explain only 20%–30% of the variability in the therapeutic dose of warfarin. Single nucleotide polymorphisms (SNPs) in the cytochrome P450 2C9 (CYP2C9) gene correlate with the clearance of S-warfarin and SNPs in the vitamin K epoxide reductase (VKORC1) gene predict warfarin sensitivity. We test the hypothesis that the combination of clinical and pharmacogenetic information can predict the therapeutic war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
96
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(112 citation statements)
references
References 0 publications
12
96
0
4
Order By: Relevance
“…Moreover, our data, consistent with previous work, indicate that the effect of the *2/*2 genotype on warfarin dose requirements is most similar to the *1/*2 and *1/*3 genotypes. 8,9 Thus these results add to the existing evidence of the association of CYP2C9 enzyme polymorphisms with decreased warfarin dose requirements. 7,37,38 An important part of this study was to determine the contribution of nongenetic factors to warfarin dose requirements.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Moreover, our data, consistent with previous work, indicate that the effect of the *2/*2 genotype on warfarin dose requirements is most similar to the *1/*2 and *1/*3 genotypes. 8,9 Thus these results add to the existing evidence of the association of CYP2C9 enzyme polymorphisms with decreased warfarin dose requirements. 7,37,38 An important part of this study was to determine the contribution of nongenetic factors to warfarin dose requirements.…”
Section: Discussionsupporting
confidence: 61%
“…7,8 Despite the evidence supporting CYP2C9 genotype and warfarin sensitivity, only a small portion of warfarin dose variability, approximately 10%, can be explained by CYP2C9-metabolizing enzyme polymorphisms. 9 Thus investigations of additional genetic predictors of warfarin dose requirements, addressing the complex interplay of proteins involved in warfarin's pharmacologic effect, are warranted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Carriers of CYP2C9 variant alleles require lower maintenance and cumulative induction doses and are more likely to exhibit supratherapeutic INR (i.e., INR43) and to experience bleeding during warfarin induction. [22][23][24][25][26][27][28][29][30] Selection of the correct warfarin dose is a challenging task, particularly during the loading period. Most physicians will attempt to tailor the dosing regimen to the patient's characteristics by taking into account the impact of factors that are known to influence warfarin pharmacokinetics and/ or pharmacodynamics.…”
mentioning
confidence: 99%
“…Polymorphisms in this gene infl uence warfarin dosing requirements and warfarin-associated bleeding ( Wittkowsky, 2002 ). It has been demonstrated that the maintenance warfarin dose can be estimated from demographic, clinical, and pharmacogenetic factors ( Gage et al, 2004 ). A second gene, VKORC1 , has been associated with the average weekly warfarin dose required to maintain patients at their desired anticoagulation target.…”
Section: A) Cyp450mentioning
confidence: 99%